Germination behaviour of Astroloma xerophyllum (Ericaceae), a species with woody indehiscent endocarps - Turner, S.; Commander, L.; Baskin, J.; Baskin, C.; Dixon, Kingsley (Wiley-Blackwell, 2009)
The dispersal unit of many Ericaceae comprises an ovoid drupe with a woody indehiscent endocarp, and diaspores of this type are notoriously difficult to germinate for most members of this widely distributed family. Within the biodiverse south-west of Western Australia, more than 200 drupaceous species of Ericaceae have been described, more than 50 of which are considered to be rare and threatened, requiring significant conservation action in the near future. In this paper, we investigate the germination ecology of the common Australian endemic, Astroloma xerophyllum, as a proxy for closely related threatened taxa, focusing on the ex situ and in situ germination requirements of seeds and indehiscent endocarps. Each endocarp possessed up to seven locules and means of 2.0-3.4 seeds per endocarp from the two collections used in this study. Seeds were up to 2.74 mm in length and 100% viable. Embryos were linear, differentiated and approximately 1.3 mm in length. Seeds within endocarps imbibed water to 28%, whereas excised seeds became hydrated to 44%. Fifty-five per cent of seeds extracted from endocarps germinated on water agar alone and 100% germinated when presoaked in gibberellic acid. Seeds remaining inside intact endocarps failed to germinate unless treated with a germination promoter and incubated for more than 20 weeks. Rapid germination of seeds in intact endocarps was promoted by soaking endocarps in gibberellic acid and incubating them in 100% O 2. Embryos grew substantially in length within seeds prior to germination, and thus seeds have morphophysiological dormancy. Seeds under natural conditions required several seasons to germinate to any degree. © 2009 The Linnean Society of London.